Analysis of Land and Water Use Efficiency: Transforming Traditional Earthen Ponds into Recirculating Aquaculture Systems (RAS) - Yuli Andriani; Aisyah Aisyah; Khalisa Muslimah (Torani Journal of Fisheries and Marine Science, 2026)
The aquaculture sector in Indonesia faces significant challenges due to the reduction of productive land and the degradation of surface water quality. This study aims to evaluate the effectiveness of transforming conventional earthen pond cultivation systems into Recirculating Aquaculture Systems (RAS) through a comprehensive analysis of land and water use efficiency. The method employed is a quantitative and qualitative descriptive approach via systematic literature review (SLR), adapting the PRISMA guidelines. Secondary data were extracted from 10 primary scientific articles published between 2016 and 2026. The results indicate that RAS technology enables extreme intensification of stocking density up to 2,000 fish/m³, significantly outperforming conventional earthen ponds (±100 fish/m³). The filtration system in RAS is proven to maintain optimal water quality stability, with very low ammonia levels (<0.01 mg/L) and high dissolved oxygen (6.0–7.2 mg/L). These conditions drive the Specific Growth Rate (SGR) to reach 2.68% and optimize the Food Conversion Ratio (FCR) to 1.08. Economically, despite high initial capital expenditure, RAS demonstrates long-term feasibility with a Payback Period of less than 4 years at an optimal commercial scale. In conclusion, the transformation to RAS technology is a strategic solution that offers superior technical, biological, and economic benefits, while ensuring ecosystem sustainability through a zero-waste concept.